2018
DOI: 10.1007/s11150-018-9414-4
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational cooperation within the household: a Public Good game with three generations

Abstract: In this paper, we analyze cooperation of individuals in a family context, using a Public Good game. In a lab experiment, 165 individuals from 55 three-generation families (youth, parent, and grandparent) play a repeated Public Good game in three different treatments: one in which three members of the same family play each other (family), a second with the youth and two non-family members, while preserving the previous generational structure (inter-generational), and a third in which three randomly-selected pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
3
7
1
Order By: Relevance
“…Contributions were influenced by gender and age. Contrasting results from previous studies, we found women to contribute more than men 31 , and older people to contribute less than young people 12,32 . Income has a less clear influence in contributions, while personal income and being the household income provider do not seem to affect contributions, having a secondary non-fishing income seems to decrease them 11 .…”
Section: Discussioncontrasting
confidence: 99%
“…Contributions were influenced by gender and age. Contrasting results from previous studies, we found women to contribute more than men 31 , and older people to contribute less than young people 12,32 . Income has a less clear influence in contributions, while personal income and being the household income provider do not seem to affect contributions, having a secondary non-fishing income seems to decrease them 11 .…”
Section: Discussioncontrasting
confidence: 99%
“…Since the external effect of present saving becomes less important over time and vanishes only in the limit, the weight on each dynasty converges to a uniform distribution. Second, the existence of cross-dynastic intergenerational altruism is consistent with findings from surveys of intergenerational time preferences (Cropper et al, 1991(Cropper et al, , 1992(Cropper et al, , 1994Johanneson and Johansson, 1997;Frederick, 2003) and experiments (Chermak and Krause, 2002;Fischer et al, 2004;Hauser et al, 2014;Molina et al, 2018; see Fehr-Duda and Fehr, 2016 for a perspective). There is also a strong empirical support for a smaller weight on the other dynasties in this generation than the own dynasty (Bernhard et al, 2006 and references therein for evidence on "parochial" altruism; see Schelling, 1995 for a perspective).…”
Section: Contribution To the Literaturesupporting
confidence: 76%
“…That is to say, under a potential positive earnings shock, women may choose to keep for themselves a small proportion of the extra income so that the traditional identity role of the husband as the main earner of the household prevails, while the opposite could operate among males. Existing research has concluded that altruism, cooperation, and collectivism are characteristic of Spanish individuals in different contexts, especially among relatives (Molina et al, 2019), and that women may be more likely to cooperate than men, especially when they cooperate with the partner (Görges, 2015). Similarly, other authors have reported gender differences in altruism and cooperation related to earnings (Cochard et al, 2018).…”
Section: Discussionmentioning
confidence: 97%